Direct gaze captures visuospatial attention - Senju, Atsushi; Hasegawa, Toshikazu (Visual cognition, 2005)
This study investigated whether the direct gaze of others influences attentional disengagement from faces in an experimental situation. Participants were required to fixate on a centrally presented face with varying gaze directions and to detect the appearance of a peripheral target as quickly as possible. Results revealed that target detection was delayed when the preceding face was directly gazing at the subject (direct gaze), as compared with an averted gaze (averted gaze) or with closed eyes (closed eyes). This effect disappeared when a temporal gap was inserted between the offset of the centrally presented face and the onset of a peripheral target, suggesting that attentional disengagement contributed to the delayed response in the direct gaze condition. The response delay to direct gaze was not found when the contrast polarity of eyes in the facial stimuli was reversed, reinforcing the importance of gaze perception in delayed disengagement from direct gaze.